REVITALISASI KEARIFAN BUDAYA BETAWI DALAM MEMPERKUAT KETAHANAN BUDAYA NASIONAL - Murtani, Hanafi (Universitas Prof. Dr. Moestopo (Beragama), 2014)
This study of the society and culture of Betawi.Â Based on the historical analysis of anthropological stretched thread of community development Betawi culture. Views on the Betawi ethnic descendants of slaves based on demographic data from the government of Batavia. The phenomenon of interpersonal communication in the context of personal communication multiethnic cultural association in the city, does not necessarily occur after Indonesian independence and became the capital city of Jakarta. This study revealed that while the growth of the city as the center of government, business and international relations, the existence of Kampung Betawi Situ Babakan become an important and strategic for the development of arts and culture as an identity Betawi Jakarta. The phenomenon of multi-ethnic association in Jakarta, especially those conducted by the Betawi people have lasted for generations of their ancestors.